Learning Curve in a Western Training Center of the Circumferential En Bloc Esophageal Endoscopic Submucosal Dissection in an In Vivo Animal Model - Tanimoto, Miguel A. (Hindawi Publishing Corporation, 2011)
Aim. Evaluate the feasibility to overcome the learning curve in a western training center of the en bloc circumferential esophageal (ECE-) ESD in an in vivo animal model. Methods. ECE-ESD was performed on ten canine models under general anesthesia on artificial lesions at the esophagus marked with coagulation points. After the ESD each canine model was euthanized and surgical resection of the esophagus and stomach was carried out according to “the Principles of Humane Experimental Technique, Russel and Burch.” The specimen was fixed with needles on cork submerged in formalin with the esophagus and stomach then delivered to the pathology department to be analyzed. Results. ECE-ESD was completed without complications in the last 3/10 animal models. Mean duration for the procedures was 192 ± 35 minutes (range 140–235 minutes). All the procedures were done at the animal lab surgery room with cardio pulmonary monitoring and artificial ventilation by staff surgery members and a staff member of the Gastroenterology department trained during 1999–2001 at the Fujigaoka hospital of the Showa U. in Yokohama, Japan, length (range 15–18 mm) and 51 ± 6.99 width (range 40–60 mm). Conclusion. ECE-ESD training is feasible in canine models for postgraduate endoscopy fellows.